Hambatan belajar peserta didik pada konsep faktor persekutuan terbesar - Cici Sumarni; Winda Ramadianti; Mardiah Syofiana; Rahmat Jumri (Mahesa Research Center, 2023)
Learning can be achieved optimally if students have no learning obstacle, so that the learning process can be carried out smoothly. If a concept is fully mastered, there will be no learning obstacle. This study aims to determine the learning obstacle that occur in the material of the greatest common factor and one way to overcome these learning obstacles is to make a didactic design. The approach used in this research is qualitative method (Didactical Design Research). Data collection techniques were carried out by giving respondent ability tests (TKR), interviews, and documentation for class VII students of a SMPN in Bengkulu City. From this study, it was found that ontogeny learning barriers, namely students experiencing obstacles regarding the prerequisite material of FPB, namely division and epistemological barriers, namely the definition of factors, common factors, and the greatest common factor.